1979
DOI: 10.1364/ao.18.000678
|View full text |Cite
|
Sign up to set email alerts
|

Pulse spreading in a single-mode fiber due to third-order dispersion

Abstract: Pulse spreading in a single-mode optical fiber is discussed taking into account the third-order dispersion term of the waveguide when the light source is modulated by a Gaussian pulse. A general expression for the pulse shape is analytically obtained, and an asymptotic approximation is used when the third-order dispersion term is small. It is also shown that the pulse width is no longer proportional to the guide length when the third-order dispersion term becomes large.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(41 citation statements)
references
References 3 publications
0
38
0
3
Order By: Relevance
“…4 of Ref. 16) to pulses shorter than 50 fsec, we find that their pulses, reflected by cavity mirrors of 0(W) t 1 X 10-41 sec 3 , begin to broaden and cause subpulses because of the enhancement of the effective value of ¢(w) [in the case of /(w), 95X enhancement occurs 18 ] by the multipass reflection in the cavity. Therefore, when ¢(o) becomes negligibly small, the pulse duration will increase more slowly in the region This behavior is similar to the dispersion dependence of the pulse duration that was analytically derived by Haus and Silberberg 1 0 but is unlike that discussed by Martinez et al 9 Therefore, in the present system, the pulse-shaping mechanism is not solitonlike.…”
mentioning
confidence: 77%
“…4 of Ref. 16) to pulses shorter than 50 fsec, we find that their pulses, reflected by cavity mirrors of 0(W) t 1 X 10-41 sec 3 , begin to broaden and cause subpulses because of the enhancement of the effective value of ¢(w) [in the case of /(w), 95X enhancement occurs 18 ] by the multipass reflection in the cavity. Therefore, when ¢(o) becomes negligibly small, the pulse duration will increase more slowly in the region This behavior is similar to the dispersion dependence of the pulse duration that was analytically derived by Haus and Silberberg 1 0 but is unlike that discussed by Martinez et al 9 Therefore, in the present system, the pulse-shaping mechanism is not solitonlike.…”
mentioning
confidence: 77%
“…The value of 4 ( w ) due to all mirrors at the above obtained optimum value of ( 0 ) for up-chirp compensation is calculated to be -1 X lop4' s3. A few research groups derived an equation describing pulse broadening due to the third-order dispersion [8], [9]. Their results showed that for the input chirpcompensated pulse, the behavior of its output pulse shape is symmetric in respect to the sign of 4 ( w ).…”
mentioning
confidence: 99%
“…así como que β µ (ω) puede expandirse en una serie de Taylor de tercer orden alrededor de la frecuencia central angular ω o , [48,49], pudiendo así estudiar tanto el fenómeno de dispersión cromática de segundo orden como el de tercer orden de manera simultánea:…”
Section: Fibra Multimodo Con Acoplo De Modosunclassified
“…Sin embargo, en el caso de enlaces de MMF que operen en regiones de longitud de ondaóptica cercana a la región de los 1300 nm para fibras de sílice, la segunda derivada resulta mínima, es decir prácticamente despreciable, β 2 µ ≈ 0 y, como consecuencia, se vuelve necesario considerar la tercera derivada d 3 β µ (ω)/dω 3 = β 3 µ de la constante de propagación a fin de obtener una descripción precisa de la respuesta en frecuencia del enlace de MMF. Los efectos de la dispersión cromática de tercer orden han sido previamente estudiados en detalle en el contexto de enlacesópticos digitales compuestos por fibra monomodo, [48][49][50][51]; al igual que diversas técnicas para su compensación, [52,53]. Para el caso de enlaces de fibra multimodo el interés principal radica en la caracterización de la respuesta en frecuencia, sin embargo hasta la actualidad no ha sido todavía publicado ningún modelo que considere la dispersión cromática de tercer orden.…”
Section: Introducción Al Modelo De Propagación Desarrolladounclassified